ANALISIS PERSEPSI DENGAN MODEL IPA PADA PEMASANG IKLAN KORAN LAMPUNG POST - Herlina Herlina (Program Pascasarjana Universitas Gajayana, 2018)
The goal to be achieved is to analyze the service attributes based on the level of expectationand level of performance according to advertisers in Lampung Post. The sample used is allthe consumers who ever put an ad in the daily newspaper Lampung Post. Analytical toolused is Importance Performance Analysis (IPA) which is used to measure the level of one'ssatisfaction on the performance of others with the Cartesian diagram as a depiction of theresults of the data. The results obtained from 23 service attributes are divided into fiveservice dimenasi 6 attributes that are considered important and determine the quality ofservice Lampung Post to advertisers are the cleanliness of Lampung Post office, the availabilityof garbage and toilets, the availability of Wifi facilities, the availability of parking, Availabilityof welcome greeters, and the tidiness of Lampung Post's physical and building forms. thesesix attributes must be more attention or even need improvement so that the company'sperformance increases and is directly proportional to the expectations of advertisers whocome directly to the office Lampung Post.